Characteristics of Fabricated Soil for Landscape Rehabilitation: The Four Crop Test for Biological Activity - Kefeli, Valentine; Leininger, Christopher; Mastalski, Shari; Kimberly, Pincin (İstanbul Kültür Üniversitesi, 2008)
Fabricated soil (FS) is a mixture of substrates containing balanced amounts of carbon, nitrogen, phosphorus, potassium and mineral elements that support plant growth . In our experiments, we use FS for the rehabilitatio n of land f r om mining soil pollutants. Characteristics of fabricated soil were determined including measurements of N, P, K; other nutritive elements including Mg, Ca, S, and Fe; and micro-elements and toxic elements including Mn, Zn, A l , Ni, and Pb. Also , microbial activity of the soil was tested to determine fungal and bacterial presence. After investigating these soil characteristics, we used a four - crop test to investigate fabricated soils and related substrates for biological activity. Soil health includes a balance of mineral and organic elements and healthy microbial activity. These characteristics play the key role in the soil ' s ability to support the growth of higher plants which complete the regenerative process of soil cycling. Healthy soils provide materials for food, energy, and shelter. Healthy soils are crucial to all biological, geological, and water cycles.
Keywords: Fabricated Soil; Fabrikasyon Toprak; Four Crop Test; Dört Kırpma Testi